Influence of Surfactants on the Mobility and Separation of Galactose, Arabinose and Rhamanose on Cellulosic Surface - Bhawani, Showkat Ahmad; Mohamad Nasir, Mohamad Ibrahim; Rokiah, Binti Hashim; Mohammad, A. (RJPBCS, 2014)
Different kinds of surfactants have been used for the study of mobility of three sugars. Mobility pattern of all three sugars viz, Galactose, Arabinose and Rhamanose has been studied in different aqueous and alcoholic eluents. An eco-friendly two-dimensional thin-layer chromatographic method was developed by using surfactants as eluents for the separation of Galactose, Arabinose and Rhamanose. Two different kinds of surfactants containing different types of charges were used for the study. Anionic surfactant (sodium cholate) was used in the first run and then the cationic surfactant (Cetyltrimethylammonium chloride) was used after rotating the plate at 90o .